Active permanent greening – a new slope greening technology based on mineral solubilizing microorganisms - Wang, Lingjian; Tang, Xinggang; Liu, Xin; Zhang, Jinchi (Frontiers in Plant Science, 2023)
With social and economic development and the associated large-scale exploitation of natural 13 resources, the number of slopes has significantly increased. As slope instability can lead to serious 14 geological disasters, the ecological protection and reconstruction of slopes has become a hot topic 15 of common global concern. In order to achieve scientific slope management and overcome the 16 difficulty of maintaining slope greening in the long term, this study explored eight strategies (A, B, 17 C, AB, AC, BC, ABC, CK), involving different patented mineral solubilizing microorganisms 18 (MSMs), and analyzed the field application of active permanent greening (APG) based on MSMs. 19 The results revealed that MSMs significantly increased the content of effective metal ions and 20 available nutrients in soil and enhanced soil enzyme activity. Among all strategies, strategy A 21 showed significant superiority, with soil effective calcium, magnesium, potassium, nitrogen, 22 phosphorus and organic matter contents increasing by 51.62%, 55.41%, 30.42%, 39.77%, 23 181.69% and 76.92%, respectively, while urease, sucrase and peroxidase activities increased by 24 89.59%, 74.68% and 85.30%. MSMs strongly promoted the growth of Amorpha. Strategy A 25 showed the best performance, with plant seedling height, ground diameter, leaf area, root length, 26 and root volume increasing by 95. 75%, 47.78%, 124.14%, 108.83%, and 139. 86%, respectively. 27 According to a comprehensive evaluation using the entropy-analysis hierarchy process, strategy A 28 has great potential for application. The field test results verified that APG has significantly better 29 greening performance than the traditional greening method, with high vegetation cover and stable 30 soil layer. The results of this study provide a reliable practical basis and technical reference for the 31 development, promotion, and application of APG. 32